Profil Kemampuan Pemahaman Konsep Siswa SMP Negeri 7 Palu dalam Menyelesaikan Soal Persamaan Garis Lurus Ditinjau dari Perbedaan Jenis Kelamin - Asveni Asveni; I Nyoman Murdiana; Ibnu Hadjar; Nurhayadi (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to describe the conceptual understanding ability of students of SMP Negeri 7 Palu in solving linear equation problems based on gender differences. This study uses a qualitative approach with a descriptive research type. The research subjects consisted of one male and one female student who have high mathematical abilities. Data were collected through a conceptual understanding test on linear equations and semi-structured interviews. Data analysis was carried out using the interactive model of Miles, Huberman, and Saldaña which includes data condensation, data presentation, and conclusion drawing. The analysis of conceptual understanding ability refers to Kilpatrick's indicators, namely restating concepts, identifying examples and non-examples, classifying objects based on certain properties, presenting concepts, and applying concepts algorithmically. The results showed that both subjects were able to meet the analyzed conceptual understanding indicators. Differences were found in the quality of understanding and accuracy in solving problems. Female students showed better accuracy in algebraic operations and provided more detailed explanations, while male students were able to choose appropriate formulas, but still experienced errors in algebraic operations. This finding shows that there are differences in the characteristics of conceptual understanding between the two subjects, even though both are in the high mathematical ability category.